Evidence-Based Treatment of Diabetic Retinopathy. (2nd January 2017) - El Rami, Hala; Barham, Rasha; Sun, Jennifer K.; Silva, Paolo S.
ABSTRACT: Diabetic retinopathy (DR) is the most frequent microvascular complication from diabetes and requires annual screening and at least annual follow-up. A systemic approach to optimize blood glucose and blood pressure may halt progression to severe stages of DR and obviate the need for ocular treatment. Although there is evidence of benefit from fenofibrate or intravitreous antiVEGF treatment for eyes with nonproliferative DR (NPDR), these therapies are not standard care for NPDR at this time. Some patients with severe NPDR, especially those with type 2 diabetes, benefit from early panretinal photocoagulation (PRP). Once DR progresses to proliferative DR (PDR), treatment is often necessary to prevent visual loss. PRP remains mainstay treatment for PDR with high-risk characteristics. However, intravitreous antiVEGF injections appear to be a safe and effective treatment alternative for PDR through at least two years. Vitreoretinal surgery is indicated for PDR cases with non-clearing vitreous hemorrhage and/or tractional retinal detachment.